The Role of Story Telling in the Development of the Child’s Lexical Richness: A Case Study - Benjelloun, Mounia; El Kirat El Allame, Yamina (International Journal of Language and Literary Studies, 2023)
As soon as children enter school, they are expected to use a relatively new and unfamiliar language to display knowledge. Literature has demonstrated that children’s early exposure to academic language at home can have a huge impact on the development of their lexical richness. This study explores the extent to which lexical richness, including lexical density and diversity are present in the production of two mothers and their children from different social and educational backgrounds during an informal storytelling interaction. The study addresses two research questions related to (i) the degree of lexical richness of the mothers’ input and their children’s output and (ii) how a mother’s social and educational background can influence the child’s lexical richness. Data analysis revealed that the use of lexical features varied considerably among the two mothers and their children. Compared to the low social and educational background mother, the affluent and well-educated mother provided her child with far more varied and denser lexical input, besides the use of interactive literacy strategies which have proven to influence the child’s output at home. The findings unveiled a strong correlation between the children’s early exposure to academic lexical input through storytelling and their academic language development.